2014
DOI: 10.21608/eajbsc.2014.16044
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical effects of Steinernema feltiae, Steinernema riobrave and Heterorhabditis bacteriophora on Spodoptera littoralis larvae

Abstract: In the present study, the infectivity of the three entomopathegnic nematodes, Steinernema feltiae, Steinernema riobrave and Heterorhabditis bacteriophora, on the cotton leafworm, Spodoptera littoralis was studied. Moreover, the effect of these pathogens on certain biochemical and physiological aspects of the host was also studied. H. bacteriophora, appeared to be more pathogenic than S. riobrave and S. feltiae to the S. littoralis larvae. The highest production (7000 infective juveniles) was obtained, where in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…riobrave and H. bacteriophora. In their study on S. littoralis, Ahmed,et al (2014) found an increasing mortality percentage of larvae with the increase in concentrations of S. feltiae, S. riobrave and H. bacteriophora. Some years later, Shaurubet al (2021) assessed the effects of some EPN strains onC.…”
Section: I2 Correlation Of the Insect Mortality With The Epn Concentr...mentioning
confidence: 92%
See 2 more Smart Citations
“…riobrave and H. bacteriophora. In their study on S. littoralis, Ahmed,et al (2014) found an increasing mortality percentage of larvae with the increase in concentrations of S. feltiae, S. riobrave and H. bacteriophora. Some years later, Shaurubet al (2021) assessed the effects of some EPN strains onC.…”
Section: I2 Correlation Of the Insect Mortality With The Epn Concentr...mentioning
confidence: 92%
“…For example, Hussaini et al (2005) found that the isolates of H. indica were more virulent than the isolate of S. carpocapsae against the A. ipsilon larvae. Some years later, H. bacteriophora was more pathogenic than S. riobrave and S. feltiae to S. littoralis larvae (Ahmed et al, 2014). Some strains of H. bacteriophora were found more virulent than S. carpocapsae strains against late 3 rd instar larvae of C. capitata (Shaurub et al, 2015).…”
Section: I5 Variable Pathogenicity Of Different Epns Against the Same...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since El-Sadawy et al (2009) demonstrated a significant decline in total protein and total lipids and alteration in different amino acids concentration in both Parasarcophaga sarchophaga and Argas persicus post treatment with H. bacteriophara and S. riobrave. Furthermore, Ahmed et al (2014) declared a significant decrease in the principle nutrients (total protein, carbohydrate, and lipid) and the activity of transaminases (GOT and GPT) of Spodoptera littoralis after treatment with H. bacteriophora and S. riobrave.…”
Section: Introductionmentioning
confidence: 99%